EFFECT OF COUNSELLING ON CONFLICT RESOLUTION SKILLS OF YOUNG ADULTS - M. SARADA DEVI, S. SRAVANTHI REDDY and (The Journal of Research, PJTSAU, 2019)
Conflict refers to some form of friction or discord arising between two individuals or within a group of members when the beliefs or actions between them are unacceptable. Men and women deal with conflicts differently. Inability of dealing conflicts often lead to distress affecting their wellbeing. The current study aimed, to find out the gender differences in conflict resolutions skills of young adults before and after counselling. To conduct the study a sample of 120 young adults belonging to the age group of 20-40 years were selected in the year 2016-17 to 2017-18. A self-measured conflict resolution questionnaire was used to analyse young adults conflict resolution skills. Highly significant differences were found between the genders with respect to emotional, financial, academic and career domains before and after counselling.Results revealed that men had better conflict resolution skills compared to women. However, there were improved mean scores noted in both genders after counselling resulting in enhanced conflict resolution skills.